Study of Environmental Preservation Law From an Islamic Legal Perspective - Firmansyah, Andi; La Ode Ismail Ahmad; Abdul Rahman Sakka (Socio Legal and Islamic Law, 2024)
Environmental preservation is becoming an increasingly urgent issue amidst global challenges posed by ecosystem degradation, pollution and climate change. In the context of Indonesia, where the majority of the population is Muslim, it is important to explore the role of Islamic law in supporting environmental conservation efforts. Islamic law, as a comprehensive legal system, not only regulates ritual and social aspects, but also provides moral and ethical guidelines related to nature conservation and ecosystem balance.This research aims to examine the principles of Islamic law that are relevant to environmental conservation and explore the potential for their application in the context of legal regulations in Indonesia. Through a qualitative approach and literature study methods, this research identifies teachings in the Al-Qur'an and Hadith which emphasize human responsibility as caliphs on earth, including the obligation to protect and preserve nature.The results of the study show that Islamic law has great potential to provide a strong ethical foundation for environmental conservation. Principles such as balance (mizan), prohibition of causing damage (fasad), and responsibility as caliph on earth can be used as a basis for formulating environmental policies and legal regulations. This research concludes that the integration of Islamic values ​​in environmental law can strengthen environmental conservation efforts in Indonesia, creating a legal framework that is not only oriented towards short-term interests but also towards long-term sustainability and balance of the ecosystem. Keywords: Islamic law, environmental conservation, environmental law